Leadership (Qawâmah) in Islamic Family a Comparative Study Between Mahmud Syaltut and Muhammad Syahrur Though - Virdausa, Ahmada Rivqy; Rahmawati, Erik Sabti (International Conference on Law, Technology, Spirituality and Society (ICOLESS); Vol 1 (2021): The 4th International Conference on Law, Technology, Spirituality and Society (ICOLESS), 2021)
Understanding the concept of Qawâmah in the family is controversial among Islamic scholars, including mutaqaddimîn and contemporary scholars. The thoughts of contemporary scholars are influenced by the issue of gender justice. As contemporary scholars, Mahmud Syaltut and Muhammad Syahrur have different concepts. This research’s objectives are: to explain the thought of Mahmud Syaltut and Muhammad Syahrur about qawâmah in the family; to identify the similarities and differences between Mahmud Syaltut and Muhammad Syahrur’s thoughts about qawâmah in the family. The type of this research is library research and using a comparative approach. This study found that Mahmud Syaltut understands qawâmah as a men’s nature as a leader for his wife because of their physical strengths and abilities. Syahrur understands qawâmah as the position of leader that can be owned by male or female as long as they have the characteristics of qawwâm which are not only from physical factors. Syaltut and Syahrur have thoughts that elevate the status of women so that they have an idea of ​​equality between men and women. Mahmud Syaltut seemed not to leave the classical thinking pattern about qawâmah truly. Syaltut’s qawâmah concept is different from Muhammad Syahrur’s thought which is different from classical thinking.